The Effectiveness of Comic Strips in Increasing Students Speaking Ability in the Second Year of Junior High School - Niâ€™matul Lailiyah; Gusti Nur Hafifah; Armeria Wijaya (Tell : Teaching of English Language and Literature Journal, 2015)
As far as the researcherâ€™s knowledge, the analysis of â€œThe Effectiveness of Comic Strips in increasing studentâ€™s speaking abilityâ€ is still difficult to find, the researcher formulates the statement of the research that is comic strips give the significant effect in increasing studentâ€™s speaking ability. The objective of research is to find out whether comic strips method can give the significant effect in increasing studentsâ€™ speaking ability or not. This research uses experimental design, the subject are VIIIth A as experimental group and VIIIth B as controlled group at MTs. Hidayatus Salam, Lowayu. The data collection uses test (pre-test and post-test) as instrument to measure the result of students. After giving the test, the researcher counts the data (percentage of the results which have the significant score) and analyses based on Criteria scoring by oral proficiency scoring categories by Brown. After giving the test of both classes, both of them have an increasing speaking ability. Based on the percentage of both classes, in post-test shows that with comic strips the experimental class has more significant effect than control class, the mean score of experimental class is 74.7 and 58.03 for control class. The experimental class has significant effect especially in the term of fluency, vocabulary, comprehensibility and performance.